Determinants of Medicine-Taking in Psychiatric Patients - Garcia-Ribera, Carlos; Bulbena, Antoni (Current Clinical Pharmacology, 2011)
Lack of adherence is a universal risk in medicine. Its consequences in terms of outcome, suffering and economic costs are immense. This is a selective review of the putative factors involved in medicine taking behavior. Adherence is multidetermined by a number of variables ranging from patient sociodemographic characteristics to factors related to patient/ psychiatrist interaction, drug tolerability and organization of care. A relevant piece of responsibility comes from the drug itself and the patient's subjective tolerability which together with the characteristics of long term treatment and insufficient insight and support result in poor or lack of adherence. The context of the patient/professional therapeutic alliance, the patient's capacities and health system availability are ultimately decisive.
Keywords: olanzapine